Creative thinking and interpersonal relations in university students - Gamarra-Moscoso, Manuel A. (2020)
The study focuses on establishing the relationship of creative thinking with the interpersonal relationships of students of the Faculty of Education and Communication Sciences. The methodology presents a quantitative approach of correlational and transversal type; the technique was the multiple response questionnaire in Likert scale; the data treatment and analysis of the results was a bivariate analysis by Pearson correlation. The results of the study determined the significant correlation, according to the results of the Pearson correlation coefficient, whose value R=0.731 with a p-value less than the degree of significance of 5%, This indicates that the degree of innovation and adaptation that students develop will directly affect their ability to interact with their peers. It is concluded that the degree of creative thinking is high in most students, which contributes to the improvement of human and interpersonal relationships in the various personal and academic activities.